2019
DOI: 10.4149/av_2019_214
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interplay between autophagy and interferon-alpha in HCV and HCV/HIV infection

Abstract: Hepatitis C virus (HCV) and human immunodeficiency virus (HIV) are among the most dangerous pathogens globally. Infection with HCV has been reported in a high percentage of HIV patients. Viruses are obligate intracellular pathogens and their survival is associated with their capability to subvert antiviral defenses of cells and to improve cellular processes required for their replication. The aim of this study was to compare the expression rate of the key gene for autophagy process, Beclin-1, as a cellular res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In HIV+ patients, the HCV viral load means were higher than in other risk groups, but this variable was not statistically significant. This may be related to the low number of HIV+ patients among the study population 21‐23 . In conclusion, genotype 1 is the predominant type among HCV genotypes and it affects 48.8% of the patients, followed by G3a (47.2%).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In HIV+ patients, the HCV viral load means were higher than in other risk groups, but this variable was not statistically significant. This may be related to the low number of HIV+ patients among the study population 21‐23 . In conclusion, genotype 1 is the predominant type among HCV genotypes and it affects 48.8% of the patients, followed by G3a (47.2%).…”
Section: Discussionmentioning
confidence: 83%
“…This may be related to the low number of HIV+ patients among the study population. [21][22][23] In conclusion, genotype 1 is the predominant type among HCV genotypes and it affects 48.8% of the patients, followed by G3a (47.2%). Our study results have indicated that in the study area the genotype distribution is similar to other parts of Iran.…”
Section: Discussionmentioning
confidence: 86%